The Aesthetic Dimension of Passion. (July 2019) - Gardner, Sebastian
Abstract: This paper is stimulated by and indebted to a study by Charles Altieri of the ways in which affect is present and articulated in art and literature, which, he argues, hold significance for the philosophy of emotion. I focus on Altieri's thesis that affective states may have aesthetic qualities and value. I pursue this notion first with reference to Nietzsche's attempt to recruit affect as a means of countering Schopenhauer's pessimism. I then attempt to show the coherence of the (on the face of it problematic) notion that passion may exhibit an aesthetic dimension, drawing on Richard Wollheim's account of certain ideas in psychoanalytic theory, for which I suggest precedents in the history of philosophy.